Violência à espreita da vida: a experiência perinatal na pandemia de Covid-19 no estado do Tocantins - Araújo, Jady Aline Albuquerque de (Universidade Federal do Tocantins, 2023)
Violations of rights and violence in the perinatal context have been denounced as routine practices for decades in Brazil, being the focus of discussions in various disciplines and social movements that together pressured the state to create laws that promote safety for women who experience perinatality. With the advent of the COVID-19 Pandemic, there was a setbackin the guarantee of perinatal rights based on the new biosafety standards. This article seeks to understand the psychological effects of the perinatal experience in the context of the COVID19 pandemic in the state of Tocantins by a user of the SUS, shedding light on the psychological impacts of perinatality experienced in a scenario of biological emergency, as well as the effects of violations of birth and postpartum rights for the perinatal experience.The research was conducted using a qualitative method, through a semi-structured investigative psychological interview. The interview was conducted online due to the advent of social distancing, a biosecurity measure against the spread of COVID-19, through the Google Meet platform. The target audience sample was a puerperal SUS user in the state of Tocantins, and the data were submitted to Bardin's content analysis, culminating in three categories of analysis: "The only fear I had was of being alone": the breaking plans and expectations during pregnancy and childbirth; “They used the pandemic to make them make their decision as if they owned the people, the owners of the truth.” Reflections on the discourse that mediates violations of law and obstetric violence; and “I'm not really strong, I can't with myself and I wouldn't be able to handle it": Repercussions of obstetric violence on the mother's self-image and bonding with the baby. maneuvers that violate the female body, inaddition to the intense psychological suffering experienced during pregnancy, childbirth and the puerperium due to the breach of expectations and plans regarding perinatality. baby, in addition to highlighting feelings such as guilt and helplessness that negatively contribute tothe self-perception of the puerperal woman